PLANNING MODEL OF TOTAL REQUIREMENTS OFFICER PERSONNEL IN SUPPORTING THE TASKS OF THE INDONESIAN NAVY - Dian Muhtar Budiasa; Ahmadi Ahmadi; Ayip Riva'i (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2022)
As the main component of national defense and security in the marine dimension, the Indonesian navy must beable to carry out organizational tasks effectively and efficiently so that the successful achievement oforganizational goals can be achieved. The main resources needed in supporting the implementation of the dutiesof the Indonesian navy are Human Resources or personnel. With an important role as a leader/supervisor indecision making and policy determination as well as organizational mobilization, it is very necessary for officerpersonnel planning in manning the entire spectrum of office space assignments in a timely manner, quality,quantity and place. The plan is a form of implementation in the Navy officer personnel development system withthe characteristics of a complex and dynamic system. Given the characteristics of the system, the researcheruses a system thinking approach analysis with the aim of articulating the problem into a causal loop diagrammodel to then be integrated into a dynamic system simulation model with the aim of getting the best policy scenarioformulation from the simulation results of the planning model for the number of officer personnel needs at the rankstrata. "C" to "H", so that the behavioral conditions of a stable personnel development system are still achievedregarding the element of the number of personnel needs in supporting the sustainability of the implementation ofthe Indonesian navy's tasks effectively and efficiently in achieving the success of organizational goals.Keywords: complex , dynamic , personnel coaching system, system thinking, dynamic system